Method for producing recycled positive electrode active material

By heating the positive electrode composite material with an alkali metal compound in a continuous furnace with opposing air flow, the method addresses the degradation issue caused by high-temperature carbon dioxide, maintaining the integrity and performance of recycled positive electrode active materials.

JP7620140B1Active Publication Date: 2025-01-22SUMITOMO CHEM CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2024054011
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2024-03-28
Publication Date
2025-01-22
Estimated Expiration
2044-03-28

AI Technical Summary

Technical Problem

The recycling of positive electrode active materials in batteries is hindered by the risk of deterioration due to high-temperature carbon dioxide generated during the heating process, which can degrade the materials.

Method used

A method involving the mixing of a positive electrode composite material with an activation treatment agent containing alkali metal compounds, followed by heating in a continuous furnace while blowing air in the opposite direction to the material flow, thereby directing carbon dioxide away from the active material and preventing high concentrations within the furnace.

Benefits of technology

This approach effectively suppresses the deterioration of the positive electrode active material by minimizing contact with high-temperature carbon dioxide, ensuring the retention of material quality and performance.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention provides a method for producing a recycled positive electrode active material, which can suppress deterioration of the positive electrode active material due to high-temperature carbon dioxide. A method for producing a recycled positive electrode active material includes the following steps. (1) A step of mixing a positive electrode mixture containing a positive electrode active material and a carbon-containing material with an activation treatment agent containing one or more alkali metal compounds to obtain a mixture. (2) A process in which the mixture is carried into a continuous furnace and heated while blowing air in the opposite direction to the direction of movement of the mixture to obtain a heated mixture. (3) A step of recovering the heated positive electrode active material from the heated mixture.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a recycled positive electrode active material. [Background technology]

[0002] The positive electrode active material of a battery contains rare metal components such as cobalt, nickel, manganese, and lithium, and in particular, the positive electrode active material of a non-aqueous electrolyte secondary battery uses a compound mainly composed of the above rare metal components. In order to conserve the resources of rare metal components, a method for reproducing the rare metal components from waste battery materials of secondary batteries is required.

[0003] For example, Patent Document 1 discloses a method for recovering a positive electrode active material by mixing a positive electrode mixture with an activation treatment agent containing an alkali metal compound, heating the mixture to decompose the binder, and removing the decomposition product and the activation treatment agent with water or the like. This method is cost-effective in that it does not use an organic solvent and directly recovers a positive electrode active material from battery waste. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2012-186150 A Summary of the Invention [Problem to be solved by the invention]

[0005] When recycling the positive electrode active material in the positive electrode mixture, the positive electrode mixture is mixed with an activation treatment agent, and the resulting mixture is heated. When the mixture is heated, the carbon-containing material in the mixture (e.g., the binder contained in the positive electrode mixture) is burned, generating carbon dioxide. The generated carbon dioxide is heated to a high temperature in a heating furnace, and it has been found that contact of the high-temperature carbon dioxide with the positive electrode active material in the mixture may cause deterioration of the positive electrode active material.

[0006] Therefore, an object of the present invention is to provide a method for producing a recycled positive electrode active material that can suppress deterioration of the positive electrode active material due to high-temperature carbon dioxide. [Means for solving the problem]

[0007] The present invention includes, for example, the following [1] to [8]. [1] A method for producing a recycled positive electrode active material, comprising the following steps: (1) A step of mixing a positive electrode mixture containing a positive electrode active material and a carbon-containing material with an activation treatment agent containing one or more alkali metal compounds to obtain a mixture. (2) A step of carrying the mixture into a continuous furnace and heating the mixture while blowing air in a direction opposite to the direction of travel of the mixture to obtain a heated mixture. (3) recovering the heated positive electrode active material from the heated mixture; [2] The manufacturing method described in [1], wherein in step (2), when the carbon dioxide concentration in the gas fed into the continuous furnace is compared with the carbon dioxide concentration in the gas exhausted from the continuous furnace, the gas exhausted from the continuous furnace has a higher carbon dioxide concentration. [3] The method according to [1] or [2], wherein in the step (2), the mixture is heated to a temperature equal to or higher than the melting point of the activation treatment agent. [4] The method according to any one of [1] to [3], wherein in the step (2), the mixture is heated to a temperature lower than the melting start temperature of the activation treatment agent. [5] The method according to any one of [1] to [4], wherein in the step (2), the continuous furnace has a region in which the temperature gradually increases along the traveling direction of the mixture. [6] The method according to any one of [1] to [5], wherein the positive electrode active material contains a lithium compound. [7] The method according to any one of [1] to [6], wherein the positive electrode active material contains a composite oxide containing at least one element selected from the following element group 1 and at least one element selected from the following element group 2: Element group 1: Ni, Co, Mn, Fe, Al, and P Element group 2: Li, Na, K, Ca, Sr, Ba, and Mg [8] The method according to any one of [1] to [7], wherein the activation treatment agent contains at least one compound selected from the group consisting of potassium compounds and sodium compounds. Effect of the Invention

[0008] According to the present invention, it is possible to provide a method for producing a recycled positive electrode active material that can suppress deterioration of the positive electrode active material due to high-temperature carbon dioxide. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] (Method of manufacturing recycled positive electrode active material) A method for producing a recycled positive electrode active material will be described below.

[0010] A method for producing a recycled positive electrode active material according to one embodiment of the present invention includes the following steps. Step (1): A step of mixing a positive electrode mixture containing a positive electrode active material and a carbon-containing material with an activation treatment agent containing one or more alkali metal compounds to obtain a mixture. Step (2): The mixture is fed into a continuous furnace and heated while blowing air in the opposite direction to the direction of the mixture's movement to obtain a heated mixture. Step (3): A step of recovering the heated positive electrode active material from the heated mixture.

[0011] According to the manufacturing method of the recycled positive electrode active material according to one embodiment, when the mixture of the positive electrode composite and the activation treatment agent is heated in a continuous furnace, the carbon dioxide generated by heating is transferred to the entrance side of the continuous furnace by sending air in the opposite direction to the moving direction of the mixture in the continuous furnace. Since the temperature in the continuous furnace generally increases from the entrance to the exit, the entrance side of the continuous furnace is a relatively low temperature area in the continuous furnace. Therefore, by transferring the carbon dioxide generated by heating to the entrance side, which is relatively low temperature in the continuous furnace, it is possible to prevent the carbon dioxide from becoming hot, and thus it is possible to suppress the contact between the high-temperature carbon dioxide and the positive electrode active material. Furthermore, by sending air in the continuous furnace, it is possible to prevent the carbon dioxide from being retained in the continuous furnace, and therefore it is possible to suppress the concentration of carbon dioxide in the continuous furnace from becoming too high. In addition, it is possible to prevent the carbon dioxide from being retained in the continuous furnace, and therefore it is possible to suppress the carbon dioxide from continuing to be heated in the continuous furnace and becoming hot. For these reasons, according to the present invention, it is possible to suppress the deterioration of the positive electrode active material due to high-temperature carbon dioxide. However, the mechanism of the present invention is not limited to the above.

[0012] Each step will be described in detail below.

[0013] Pre-process (A): Positive electrode composite preparation process First, a positive electrode mixture containing a positive electrode active material and a carbon-containing material is prepared.

[0014] In the positive electrode mixture, the particles of the positive electrode active material may be bound to each other by a binder. The positive electrode mixture may contain a conductive material and / or an electrolyte in addition to the positive electrode active material and the binder. When the positive electrode mixture contains a conductive material, the particles of the positive electrode active material and the conductive material may be bound to each other by a binder. The electrolyte is a component that originates from the electrolyte of the battery and is impregnated into the positive electrode mixture. The positive electrode mixture may contain a fluorine compound that originates from the binder and / or the electrolyte (e.g., the electrolyte in the electrolyte).

[0015] [Cathode active material] Examples of the positive electrode active material include composite compounds containing one or more of the following elements as constituent elements: lithium, oxygen, fluorine, sodium, magnesium, aluminum, silicon, phosphorus, sulfur, potassium, calcium, titanium, vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, gallium, yttrium, niobium, molybdenum, silver, indium, and tungsten.

[0016] The positive electrode active material may be composed of only a single compound, or may be composed of a plurality of compounds.

[0017] The positive electrode active material preferably contains a composite oxide containing at least one element selected from element group 1 below and at least one element selected from element group 2 below. Element group 1: Ni, Co, Mn, Fe, Al, and P Element group 2: Li, Na, K, Ca, Sr, Ba, and Mg

[0018] The positive electrode active material preferably contains a compound represented by the following formula (A).

[0019] Li 1+a M 2 b M 1 M T c O 2+d X e (A) However, M 2 represents at least one element selected from the group consisting of Na, K, Ca, Sr, Ba, and Mg; M 1 represents at least one element selected from the group consisting of Ni, Co, Mn, Fe, Al, and P; M T represents at least one element selected from the group consisting of Ni, Co, Mn, and transition metal elements excluding Fe, X represents at least one element selected from the group consisting of nonmetallic elements other than O and P; -0.4 < a < 1.5, 0 ≤ b < 0.5, 0 ≤ c < 0.5, -0.5 < d < 1.5, and 0 ≤ e < 0.5 are satisfied.

[0020] M T is preferably at least one element selected from the group consisting of Cu, Ti, Mg, Al, W, Mo, Nb, Zn, Sn, Zr, Ga, V, B, Si, Ca, Sr, Ba, Ge, Cr, Sc, Y, La, Ta, Tc, Ru, Rh, Pd, Ag, Cd, and In. Examples of X include F, S, Cl, Br, I, Se, Te, N, etc.

[0021] The positive electrode active material preferably contains a composite oxide containing at least Li and Ni.

[0022] In the positive electrode active material, M 1 the molar fraction of Ni is preferably 0.3 to 0.95.

[0023] The crystal structure of the positive electrode active material (for example, composite oxide) is not particularly limited, but a layered structure is preferred, and a hexagonal or monoclinic crystal structure is more preferred.

[0024] The hexagonal crystal structure is P3, P3 1 , P3 2 , R3, P-3, R-3, P312, P321, P3 1 12, P3 1 21, P3 2 12, P3 2 21, R32, P3m1, P31m, P3c1, P31c, R3m, R3c, P-31m, P-31c, P-3m1, P-3c1, R-3m, R-3c, P6, P6 1 , P6 5 , P6 2 , P6 4 , P6 3 , P-6, P6 / m, P6 3 / m, P622, P6 1 22, P6 5 22, P6 2 , P6 4 , P6 3 22, P6mm, P6cc, P63 cm, P6 3 mc, P-6m2, P-6c2, P-62m, P-62c, P6 / mmm, P6 / mcc, P6 3 / mcm and P6 3 / mmc.

[0025] The monoclinic crystal structure is P2, P2 1 , C2, Pm, Pc, Cm, Cc, P2 / m, P2 1 / m, C2 / m, P2 / c, P2 1 It belongs to any one space group selected from the group consisting of C2 / c and C3 / c.

[0026] The crystal structure of the positive electrode active material preferably belongs to the space group R-3m contained in a hexagonal crystal structure, or the space group C2 / m contained in a monoclinic crystal structure.

[0027] The crystal structure of the positive electrode active material can be identified from a powder X-ray diffraction pattern obtained by powder X-ray diffraction measurement using CuKα radiation as a radiation source.

[0028] The particle size of the positive electrode active material in the positive electrode mixture is not particularly limited, but may be about 0.001 to 100 μm. The particle size distribution of the positive electrode active material can be measured using a laser diffraction scattering particle size distribution measuring device (e.g., Mastersizer 2000, manufactured by Malvern Instruments). A volume-based cumulative particle size distribution curve is created from the particle size distribution, and the particle size (D50) value at 50% accumulation from the fine particle side can be regarded as the average particle size of the positive electrode active material.

[0029] There is no particular limitation on the content of the positive electrode active material in the positive electrode mixture.

[0030] [Carbon-containing materials] Examples of the carbon-containing material contained in the positive electrode mixture include a binder, a conductive material (carbon-based conductive material), and an electrolyte. When the positive electrode mixture contains a binder, particles of the positive electrode active material may be bound to each other by the binder in the positive electrode mixture.

[0031] Examples of the binder (binder before activation treatment) include thermoplastic resins, etc. Specific examples include fluororesins such as polyvinylidene fluoride (hereinafter sometimes referred to as "PVdF"), polytetrafluoroethylene (PTFE), tetrafluoroethylene-hexafluoropropylene-vinylidene fluoride copolymers, hexafluoropropylene-vinylidene fluoride copolymers, and tetrafluoroethylene-perfluorovinyl ether copolymers; polyolefin resins such as polyethylene and polypropylene; and styrene-butadiene copolymers (SBR). The binder may be used alone or in combination of two or more kinds.

[0032] The content of the binder in the positive electrode mixture is not particularly limited, but may be in the following ranges relative to 100 parts by mass of the positive electrode active material. The content of the binder may be 0.5 parts by mass or more, 1 part by mass or more, or 2 parts by mass or more. The content of the binder may be 30 parts by mass or less, 10 parts by mass or less, or 5 parts by mass or less. From these viewpoints, the content of the binder may be 0.5 to 30 parts by mass, 1 to 10 parts by mass, 1 to 5 parts by mass, or 2 to 5 parts by mass.

[0033] [Conductive material] Examples of the conductive material include metal-based conductive materials such as metal particles; and carbon-based conductive materials made of carbon materials.

[0034] Specific examples of carbon-based conductive materials include graphite powder, carbon black (eg, acetylene black), and fibrous carbon materials (eg, graphitized carbon fibers and carbon nanotubes).

[0035] The carbon-based conductive material may be a single carbon material, or may be composed of a plurality of carbon materials.

[0036] The specific surface area of ​​the carbon material used as the carbon-based conductive material is 0.1 to 500 m 2 In this case, the conductive material may have a specific surface area of ​​30 m 2 / g or more, and is made of only carbon-based conductive materials with a specific surface area of ​​30 m 2 / g or more, and may be carbon black having a specific surface area of ​​30 m 2 When an activating treatment agent containing an alkali metal compound having an oxidizing power, which will be described later, is used, the rate of oxidation treatment of the carbon-based conductive material can be increased, and even a carbon material having a small specific surface area can be oxidized in some cases.

[0037] The content of the conductive material in the positive electrode mixture is not particularly limited, but may be in the following ranges relative to 100 parts by mass of the positive electrode active material. The content of the conductive material may be 0 parts by mass or more, more than 0 parts by mass, 1 part by mass or more, 3 parts by mass or more, or 5 parts by mass or more. The content of the conductive material may be 50 parts by mass or less, 40 parts by mass or less, 30 parts by mass or less, 20 parts by mass or less, or 10 parts by mass or less. From these viewpoints, the content of the conductive material may be 0 to 50 parts by mass, more than 0 parts by mass and 40 parts by mass or less, 1 to 30 parts by mass, 1 to 10 parts by mass, 3 to 20 parts by mass, or 5 to 10 parts by mass.

[0038] The positive electrode mixture may contain a metal-based conductive material such as metal particles and / or an electrolyte in addition to the positive electrode active material and the carbon-containing material. When the positive electrode mixture contains a binder and a conductive material, the particles of the positive electrode active material and the conductive material may be bound to each other by the binder. The electrolyte is a component that is derived from the electrolyte of the battery and is impregnated into the positive electrode mixture. The positive electrode mixture may contain a fluorine compound derived from the binder and / or the electrolyte (e.g., the electrolyte in the electrolyte).

[0039] [Electrolytes and Solvents] An example of an electrolyte is LiPF 6 , LiBF 4 , LiClO 4 , LiN(SO 2 CF 3 ) 2 , LiN(SO 2 F) 2 , LiCF 3 SO 3 The content of the electrolyte contained in the positive electrode mixture is not particularly limited, but may be 0.0005 to 7 mass %.

[0040] The positive electrode mixture may contain a solvent derived from the electrolyte, such as dimethyl carbonate, diethyl carbonate, or ethyl methyl carbonate.

[0041] [Recovery of cathode mixture] The positive electrode mixture can be obtained by separating and recovering the positive electrode mixture layer from a waste positive electrode having a current collector and a positive electrode mixture layer.

[0042] The "scrap positive electrodes" may be positive electrodes recovered from discarded batteries, and waste positive electrodes generated during the manufacturing process of positive electrodes or batteries. The discarded batteries may be used batteries, or unused but non-standard batteries. The waste positive electrodes may be the ends of positive electrodes generated during the manufacturing process of batteries, or non-standard positive electrodes. As the positive electrode composite, waste positive electrode composite not attached to a current collector (waste generated during the manufacturing process of the positive electrode composite) may also be used.

[0043] The waste positive electrode has a current collector which is a metal foil such as aluminum foil or copper foil, and a positive electrode mixture layer provided on the current collector. The positive electrode mixture layer may be provided on one side or both sides of the current collector.

[0044] Examples of a method for separating the positive electrode mixture layer from a waste positive electrode having a current collector and a positive electrode mixture layer include a method for mechanically peeling the positive electrode mixture layer from the current collector (e.g., a method for scraping the positive electrode mixture layer from the current collector), a method for penetrating a solvent into the interface between the current collector and the positive electrode mixture layer to peel the positive electrode mixture layer from the current collector, a method for dissolving the current collector using an alkaline or acidic aqueous solution to separate the positive electrode mixture layer, etc. The method for mechanically peeling the positive electrode mixture layer from the current collector is preferred.

[0045] Previous process (B): Positive electrode mixture cleaning process Next, when the positive electrode mixture contains an electrolyte, it is preferable to bring the prepared positive electrode mixture into contact with an electrolyte washing solvent to remove at least a part of the electrolyte from the positive electrode mixture. Specifically, the positive electrode mixture containing the positive electrode active material, the carbon-containing material, etc. is brought into contact with the electrolyte washing solvent to obtain a slurry containing a solid component and a liquid component, and then the slurry is separated into the solid component and the liquid component.

[0046] Solid-liquid separation is an operation for separating a slurry into a solid component and a liquid component. Examples of the method for solid-liquid separation may be conventionally known methods, such as filtration and centrifugation.

[0047] The electrolyte cleaning solvent is not particularly limited. Examples of the electrolyte cleaning solvent include carbonates such as ethylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, and propylene carbonate; water; ketones such as acetone, methyl ethyl ketone, diethyl ketone, and methyl isobutyl ketone; and alcohols such as ethanol, methanol, propanol, and isopropyl alcohol.

[0048] The positive electrode mixture can be brought into contact with the electrolyte washing solvent in a known contact device for powder and liquid (for example, a stirring tank).

[0049] In the step of contacting the positive electrode mixture with the electrolyte washing solvent, it is preferable to obtain a slurry by stirring the positive electrode mixture and the electrolyte washing solvent. The peripheral speed of the tip of the stirring blade may be 0.1 to 1.0 m / s.

[0050] In the washing step of the positive electrode composite material, after solid-liquid separation, the solid component may be rinsed. The rinsing is an operation in which the solid component is again brought into contact with the electrolyte washing solvent to obtain a slurry, and the slurry is again separated into a solid component and a liquid component. In the washing step of the positive electrode composite material, rinsing may be performed multiple times. The slurry concentration in the rinsing can be adjusted as desired. In the rinsing, the slurry can also be stirred as described above.

[0051] The above-mentioned washing can sufficiently remove the electrolyte from the positive electrode mixture. For example, if the electrolyte remains, the following reaction occurs, and the structure of the positive electrode active material may change from a layered rock salt structure to a spinel structure. LiPF 6 +16LiMO 2 +2O 2 → 6LiF+Li 3 PO 4 +8LiM 2 O 4

[0052] Furthermore, when the activation treatment agent contains lithium carbonate, lithium may be consumed through the following reaction. LiPF 6 +4Li 2 CO 3 → 6LiF+Li 3 PO 4 +4CO 2

[0053] The separated solid component may be dried to remove the electrolyte washing solvent by reducing pressure and / or heating, if necessary. The heating temperature may be 50 to 200°C.

[0054] Step (1): Activation treatment agent mixing step Next, the prepared positive electrode mixture and an activation treatment agent containing one or more types of alkaline compounds are mixed to obtain a mixture.

[0055] The method for mixing the positive electrode mixture and the activation treatment agent may be either dry mixing or wet mixing, or a combination of these mixing methods. The order in which the positive electrode mixture and the activation treatment agent are mixed is not particularly limited.

[0056] During mixing, it is preferable to use a mixer equipped with mixing media such as balls and to carry out a pulverizing and mixing step, which can improve the mixing efficiency.

[0057] As a mixing method, dry mixing is preferred because mixing can be performed more easily. In dry mixing, a V-type mixer, a W-type mixer, a ribbon mixer, a drum mixer, a powder mixer equipped with an internal stirring blade, a ball mill, a vibration mill, or a combination of these devices can be used.

[0058] As a mixer used for dry mixing, a powder mixer equipped with an internal stirring blade is preferable, and a specific example thereof is a Loedige Mixer (manufactured by Matsubo Corporation).

[0059] The activation treatment agent used in this step will be described in detail below.

[0060] <Activation treatment agent> The activation treatment agent contains one or more alkali metal compounds. The activation treatment agent preferably contains at least one compound selected from the group consisting of potassium compounds and sodium compounds. Here, potassium and / or sodium may be referred to as alkali metal element X. The activation treatment agent may contain an alkali metal compound containing another alkali metal such as Li in addition to the potassium compound and / or sodium compound.

[0061] When the activation treatment agent comes into contact with the positive electrode active material, the positive electrode active material can be activated. In particular, when the alkali metal compound in the activation treatment agent contains a molten portion, the contact between the molten portion and the positive electrode active material is improved, and the activation of the positive electrode active material is further promoted.

[0062] In addition, the positive electrode mixture may contain a compound containing fluorine derived from the binder and / or the electrolyte, but by contacting the compound containing fluorine with the activation treatment agent, the fluorine component is stabilized as an alkali metal fluoride, so that the generation of corrosive gases such as hydrogen fluoride can be suppressed. Note that it is desirable to prevent the generation of hydrogen fluoride, since it reduces the activity of the positive electrode active material.

[0063] The proportion of all alkali metal compounds in the activation treatment agent is appropriately set taking into consideration the type of alkali metal compound and the type of target positive electrode active material, etc., and is usually 50 mass% or more, preferably 70 mass% or more, relative to the total mass of the activation treatment agent, and may be 100 mass% (an embodiment in which the activation treatment agent is essentially composed of alkali metal compounds).

[0064] The concentration of at least one alkali metal selected from the group consisting of potassium and sodium in the alkali metals contained in the alkali metal compound can be adjusted arbitrarily within the range of 0 to 100 mol%, but is preferably 10 mol% or more, more preferably 20 mol% or more, and is preferably 90 mol% or less, more preferably 80 mol% or less.

[0065] Examples of alkali metal compounds that are components of the activation treatment agent include alkali metal hydroxides, borates, carbonates, oxides, peroxides, superoxides, nitrates, phosphates, sulfates, chlorides, vanadates, bromates, molybdates, and tungstates, etc. These can be used alone or in combination as components of the activation treatment agent.

[0066] Specific examples of suitable alkali metal compounds include hydroxides such as LiOH, NaOH, KOH, RbOH, CsOH, etc.; LiBO 2 , NaBO 2 , K.B.O. 2 , RbBO 2 , CsBO 2 borate etc.; Li 2 CO 3 , Na 2 CO 3 , K 2 CO 3 , RbCO 3 , CsCO 3 etc. carbonates; Li 2 O, Na 2 OK 2 O, Rb 2 O, Cs 2 Oxides such as O; Li2 O 2 , Na 2 O 2 , K 2 O 2 , Rb 2 O 2 , Cs 2 O 2 Peroxides etc.; LiO 2 , NaO 2 , K.O. 2 , RbO 2 , CsO 2 etc. superoxide; LiNO 3 , NaNO 3 , KNO 3 , RbNO 3 , CsNO 3 Nitrates etc.; Li 3 PO 4 , Na 3 PO 4 , K 3 PO 4 , Rb 3 PO 4 , Cs 3 PO 4 Phosphates, etc.; Li 2 SO 4 , Na 2 SO 4 , K 2 SO 4 , Rb 2 SO 4 , Cs 2 SO 4 Sulfates, etc.; Chlorides such as LiCl, NaCl, KCl, RbCl, CsCl; Bromides such as LiBr, NaBr, KBr, RbBr, CsBr, etc.; LiVO 3 , NaVO 3 , K.V.O. 3 , RbVO 3 , CsVO 3 vanadates, etc.; Li 2 MoO 4 , Na 2 MoO 4 , K 2 MoO4 , Rb 2 MoO 4 , CsMoO 4 Molybdates such as; Li 2 WO 4 , Na 2 WO 4 , K 2 WO 4 , Rb 2 WO 4 , CsWO 4 tungstates such as;

[0067] Here, in order to further enhance the activation effect of the positive electrode active material, the activation treatment agent may contain, in addition to at least one compound selected from the group consisting of potassium compounds and sodium compounds, the same alkali metal element as the alkali metal element contained in the positive electrode active material in the positive electrode mixture.

[0068] That is, when the positive electrode active material in the positive electrode mixture is a lithium composite oxide, it is preferable that the activation treatment agent contains a lithium compound in addition to at least one compound selected from the group consisting of potassium compounds and sodium compounds. Suitable lithium compounds include LiOH, LiBO 2 , Li 2 CO 3 , Li 2 O, Li 2 O 2 , LiO 2 , LiNO 3 , Li 3 PO 4 , Li 2 SO 4 , LiCl, LiVO 3 , LiBr, Li 2 MoO 4 , and Li 2 WO 4 Examples include:

[0069] The activation treatment agent may contain a compound other than an alkali metal compound as necessary. Examples of the compound other than an alkali metal compound include alkaline earth metal compounds containing alkaline earth metal elements such as magnesium, calcium, barium, etc. The alkaline earth metal compound is contained in the activation treatment agent together with the alkali metal compound for the purpose of controlling the melting start temperature of the activation treatment agent.

[0070] In addition, the content of compounds other than the alkali metal compound in the activation treatment agent is selected within a range that does not significantly suppress the effects derived from the above-mentioned molten alkali metal compound, and can be less than 50 mass% relative to the total mass of the activation treatment agent.

[0071] The amount of the activation treatment agent added in the mixture of the positive electrode mixture and the activation treatment agent is preferably 0.001 to 100 times, and more preferably 0.05 to 1 time, the mass of the positive electrode active material contained in the positive electrode mixture.

[0072] When the activation treatment agent contains a potassium compound and a lithium compound, the ratio of the lithium content (molar) to the potassium content (molar) (lithium content / potassium content) may be 0.01 to 100, 0.1 to 10, or 0.2 to 4, from the viewpoint of making the charge / discharge characteristics of a battery produced using the recycled positive electrode active material more comparable to the charge / discharge characteristics of a battery produced using an unused positive electrode active material.

[0073] When the activation treatment agent contains a sodium compound and a lithium compound, the ratio of the lithium content (molar basis) to the sodium content (molar basis) (lithium content / sodium content) may be 0.01 to 100, 0.1 to 10, or 0.2 to 4, from the viewpoint of making the charge / discharge characteristics of a battery produced using the recycled positive electrode active material more comparable to the charge / discharge characteristics of a battery produced using an unused positive electrode active material.

[0074] When the activation treatment agent contains a potassium compound, the potassium content (molar) contained in the activation treatment agent may be 1% or more and less than 500%, 10% or more and less than 400%, 50% or more and less than 300%, 100% or more and less than 250%, or 150% or more and less than 250% of the fluorine content (molar) contained in the positive electrode composite, from the viewpoint of making the charge / discharge characteristics of a battery manufactured using the recycled positive electrode active material more similar to the charge / discharge characteristics of a battery manufactured using an unused positive electrode active material.

[0075] When the activation treatment agent contains a sodium compound, the sodium content (molar) contained in the activation treatment agent may be 1 to 200%, 10 to 200%, 50 to 200%, or 100 to 200%, 1% or more and less than 150%, 10% or more and less than 150%, 50% or more and less than 150%, or 100% or more and less than 150%, relative to the fluorine content (molar) contained in the positive electrode composite, from the viewpoint of making the charge / discharge characteristics of a battery produced using the recycled positive electrode active material more comparable to the charge / discharge characteristics of a battery produced using an unused positive electrode active material.

[0076] The number of moles of the alkali metal compound in the activation treatment agent in the mixture of the positive electrode composite and the activation treatment agent can be added so that the number of moles of the alkali metal element is 0.001 to 200 times the number of moles of the positive electrode active material (e.g., Formula A) contained in the positive electrode composite.

[0077] By appropriately controlling the ratio of the activation treatment agent in the mixture, the cost of recovering the positive electrode active material from the positive electrode mixture can be reduced, and the oxidative decomposition treatment speed of the carbon-containing material (carbon-based conductive material, binder, etc.) can be increased. In addition, the effect of preventing the generation of corrosive gas in the heating step can be improved, and further the discharge capacity of the battery manufactured using the obtained positive electrode active material can be increased.

[0078] At least one of the alkali metal compounds contained in the activation treatment agent is preferably an alkali metal compound that exhibits alkalinity when dissolved in water. When an activation treatment agent containing such an alkali metal compound is dissolved in pure water, the pH of the solution becomes greater than 7. Hereinafter, such an activation treatment agent may be referred to as an "alkaline activation treatment agent."

[0079] By using an alkaline activation treatment agent, it is possible to further suppress the generation of corrosive gases during the heating process, and therefore it is possible to further increase the discharge capacity of a battery manufactured using the recovered positive electrode active material. In addition, by using an alkaline activation treatment agent, it is possible to increase the treatment speed of carbon-containing materials (carbon-based conductive materials, binders, etc.).

[0080] Examples of alkali metal compounds that exhibit alkalinity when dissolved in water and are contained in the alkaline activation treatment agent include hydroxides, carbonates, hydrogen carbonates, oxides, peroxides, and superoxides of alkali metals. Specifically, hydroxides such as LiOH, NaOH, KOH, RbOH, and CsOH; Li 2 CO 3 , Na 2 CO 3 , K 2 CO 3 , RbCO 3 , CsCO 3 Carbonates such as LiHCO 3 , NaHCO 3 , K.H.C.O. 3 , RbHCO 3 , CsHCO 3 etc.; Li 2 O, Na 2 OK 2 O, Rb 2 O, Cs 2 Oxides such as Li 2 O 2 , Na 2 O 2 , K 2 O 2 , Rb 2 O 2 , Cs 2 O 2Peroxides such as LiO 2 , NaO 2 , K.O. 2 , RbO 2 , CsO 2 One or more of these may be contained in the activation treatment agent.

[0081] In addition, when the conductive material contained in the positive electrode composite is a carbon-based conductive material, at least one of the alkali metal compounds contained in the activation treatment agent may be an alkali metal compound having an oxidizing power that oxidizes and decomposes the carbon-based conductive material at the temperature of the heating step. Hereinafter, an activation treatment agent containing such an alkali metal compound may be referred to as an "activation treatment agent having an oxidizing power."

[0082] Use of an activation treatment agent having such oxidizing power is particularly effective in promoting the oxidation of the conductive material, which is a carbon material, to carbon dioxide, and promoting the oxidation of the binder, which is a hydrocarbon material, to carbon dioxide and water vapor, and can further increase the discharge capacity of a battery manufactured using the obtained positive electrode active material, and can also improve the effect of preventing the generation of corrosive gases during the heating process.

[0083] Examples of alkali metal compounds having the oxidizing power required to oxidize carbonaceous conductive materials and hydrocarbons to carbon dioxide and water vapor include alkali metal peroxides, superoxides, nitrates, sulfates, vanadates, and molybdates, which may be used alone or in combination of two or more.

[0084] Specifically, Li 2 O 2 , Na 2 O 2 , K 2 O 2 , Rb 2 O 2 , Cs 2 O 2 Superoxides such as LiO 2 , NaO 2 , K.O. 2 , RbO 2 , CsO 2;LiNO 3 , NaNO 3 , KNO 3 , RbNO 3 , CsNO 3 Nitrates such as Li 2 SO 4 , Na 2 SO 4 , K 2 SO 4 , Rb 2 SO 4 , Cs 2 SO 4 Sulfates such as LiVO 3 , NaVO 3 , K.V.O. 3 , RbVO 3 , CsVO 3 vanadates such as Li 2 MoO 4 , Na 2 MoO 4 , K 2 MoO 4 , Rb 2 MoO 4 , CsMoO 4 Molybdates such as;

[0085] Details of the oxidizing power of these alkali metal compounds are described in JP 2012-186150 A.

[0086] The alkali metal compound may be a carbonate or sulfate from the viewpoint of making it easier to make the charge / discharge characteristics of a battery produced using the recycled positive electrode active material more comparable to those of a battery produced using an unused positive electrode active material, and Li 2 CO 3 , Na 2 SO 4 , Na 2 CO 3 , and K 2 CO 3 It may be at least one selected from the group consisting of:

[0087] Process (2): Heating process Step (2) (heating step) is a step of carrying the mixture obtained in step (1) (hereinafter, sometimes referred to as the "mixture before heating") into a continuous furnace, heating the mixture before heating while feeding air in the opposite direction to the direction of movement of the mixture before heating in the continuous furnace to obtain a mixture after heating. By feeding air in the opposite direction to the direction of movement of the mixture before heating in the continuous furnace, carbon dioxide generated by heating the carbon-containing material (carbon-based conductive material, binder, etc.) can be transferred to the inlet side of the continuous furnace, and contact between the high-temperature carbon dioxide and the positive electrode active material can be suppressed. In addition, by feeding air in the continuous furnace, it is possible to prevent carbon dioxide from stagnation in the continuous furnace, and therefore it is possible to suppress the increase in the concentration and temperature of carbon dioxide in the continuous furnace.

[0088] The mixture before heating may be heated to a temperature equal to or higher than the melting initiation temperature (Tmp) of the activation treatment agent, or may be heated to a temperature lower than the melting initiation temperature (Tmp) of the activation treatment agent.

[0089] "Melting start temperature (Tmp) of the activation treatment agent" means the lowest temperature at which a part of the activation treatment agent exhibits a liquid phase. The melting start temperature of the activation treatment agent is a value determined by differential thermal analysis (DTA). That is, when 5 mg of the mixture before heating is subjected to differential thermal analysis (DTA, measurement conditions: heating rate: 10°C / min), the melting start temperature is the temperature at which the DTA signal shows an endothermic peak.

[0090] The melting start temperature of the activation treatment agent is preferably 700° C. or lower, and more preferably 600° C. or lower. There is no lower limit to the melting start temperature of the activation treatment agent, but it may be, for example, 150° C. or higher.

[0091] The melting point of the activation treatment agent means the lowest temperature at which a part of the activation treatment agent becomes liquid when the activation treatment agent alone is heated. By mixing the positive electrode composite material and the activation treatment agent, the melting start temperature of the activation treatment agent becomes lower than the melting point of the activation treatment agent.

[0092] The melting point of the activation treatment agent is a value determined by differential thermal analysis (DTA). Specifically, 5 mg of the activation treatment agent is subjected to differential thermal analysis (DTA, measurement conditions: heating rate: 10°C / min), and the temperature at which the DTA signal shows an endothermic peak is defined as the melting point of the activation treatment agent.

[0093] The continuous furnace has at least an inlet for carrying in the mixture before heating and an outlet for carrying out the mixture after heating. Examples of the continuous furnace include a gas furnace, an electric furnace, an infrared heating furnace, a plasma heat treatment furnace, a heavy oil furnace, a light oil furnace, a hydrogen heat treatment furnace, an induction heating furnace, a walking beam furnace, a mesh belt furnace, a continuous rotary kiln furnace, and a continuous shuttle kiln furnace. The continuous furnace may have an air inlet for feeding air, and may have an exhaust port for exhausting carbon dioxide and the like. The continuous furnace may have multiple air inlets and may have multiple exhaust ports.

[0094] When the continuous furnace has an air inlet and / or an exhaust port, the location of the air inlet and / or the exhaust port in the continuous furnace may be determined according to the structure of the continuous furnace, the amount of the mixture before heating, the components contained in the gas to be supplied, the amount of carbon dioxide generated in the continuous furnace, etc. For example, multiple air inlets may be arranged on the discharge side of the continuous furnace, and multiple exhaust ports may be arranged on the inlet side of the continuous furnace, or the air inlets and exhaust ports may be arranged alternately along the traveling direction of the mixture. The air inlets may be arranged to face the exhaust ports, or may be arranged not to face the exhaust ports.

[0095] The air is fed into the continuous furnace in the opposite direction to the direction of travel of the mixture in the continuous furnace. In other words, the air is fed into the continuous furnace along the direction from the discharge outlet side to the inlet side. The air is fed into the continuous furnace, for example, from the air feed port provided on the discharge outlet side to the exhaust port provided on the inlet side. The air may be fed into the continuous furnace not only in the opposite direction to the direction of travel of the mixture in the continuous furnace, but also in the direction perpendicular to the direction of travel of the mixture in the continuous furnace, from the viewpoint of increasing the exhaust efficiency of carbon dioxide and further suppressing the deterioration of the positive electrode active material due to high-temperature carbon dioxide.

[0096] The gas supply into the continuous furnace may be performed in the entire continuous furnace or in only a part of the continuous furnace. The gas supply into the continuous furnace may be performed in a temperature region where the amount of carbon dioxide generated in the continuous furnace is large, from the viewpoint of increasing the exhaust efficiency of carbon dioxide and further suppressing the deterioration of the positive electrode active material due to high-temperature carbon dioxide. For example, the gas supply may be performed in a region where the temperature in the continuous furnace is 300 to 900°C, 300 to 700°C, or 300 to 600°C. The gas supply into the continuous furnace is preferably performed in a region where the temperature is lower than the melting start temperature of the activation treatment agent.

[0097] When the temperature at which the amount of carbon dioxide generated in the continuous furnace is large is lower than the melting start temperature of the activation treatment agent, the air supply into the continuous furnace may be performed in a temperature range below the melting start temperature of the activation treatment agent in the continuous furnace, and when the temperature at which the amount of carbon dioxide generated in the continuous furnace is higher than the melting start temperature of the activation treatment agent, the air supply into the continuous furnace may be performed in a temperature range higher than the melting start temperature of the activation treatment agent in the continuous furnace.

[0098] The air may be fed in a direction other than the opposite direction to the direction of movement of the mixture in the continuous furnace. For example, the air may be fed in a direction perpendicular to the direction of movement of the mixture. That is, another embodiment of the present invention is a method for producing a recycled positive electrode active material, comprising the following steps. Step (1): A step of mixing a positive electrode mixture containing a positive electrode active material and a carbon-containing material with an activation treatment agent containing one or more alkali metal compounds to obtain a mixture. Step (2): A step of introducing the mixture into a continuous furnace and heating the mixture while blowing air in a direction perpendicular to the direction of movement of the mixture to obtain a heated mixture. Step (3): A step of recovering the heated positive electrode active material from the heated mixture.

[0099] The gas sent into the continuous furnace is not particularly limited, and may be, for example, an oxygen-containing gas such as air, or an inert gas such as nitrogen or argon. The gas sent into the continuous furnace is exhausted together with the carbon dioxide generated in the continuous furnace. Therefore, when comparing the carbon dioxide concentration in the gas sent into the continuous furnace with the carbon dioxide concentration in the gas exhausted from the continuous furnace, the carbon dioxide concentration in the gas exhausted from the continuous furnace is higher. The gas exhausted from the continuous furnace may be sent into the continuous furnace again after removing carbon dioxide.

[0100] The flow rate of the gas per 1 L of heating space sent into the continuous furnace may be, for example, 0.001 to 1.0 L / min or 0.01 to 0.6 L / min. The flow rate of the gas per 1 L of heating space can be appropriately adjusted depending on the structure of the continuous furnace, the amount of the mixture before heating, the components contained in the gas sent, the amount of carbon dioxide generated in the continuous furnace, and the like. For example, the flow rate of the gas per 1 L of heating space may be adjusted to be large from the viewpoint of further suppressing the deterioration of the positive electrode active material by lowering the concentration of carbon dioxide in the continuous furnace, and the flow rate of the gas per 1 L of heating space may be adjusted to be small from the viewpoint of increasing energy efficiency by suppressing the temperature drop in the continuous furnace due to the gas sent. In addition, the flow rate of the gas per 1 L of heating space may be adjusted to an amount such that the carbon dioxide concentration per 1 L of heating space is a specific value or less (for example, 10 volume % or less). The flow rate of the gas per 1 L of heating space sent into the continuous furnace may be approximately the same throughout the continuous furnace, or may be different at each point of the continuous furnace.

[0101] The continuous furnace may be equipped with a means for separating or removing carbon dioxide (for example, a device for separating or removing carbon dioxide) from the viewpoint of lowering the carbon dioxide concentration in the continuous furnace. Examples of the means for separating or removing carbon dioxide include a carbon dioxide adsorbent, a carbon dioxide absorbent, and a carbon dioxide separation membrane.

[0102] The residence time of the mixture in the continuous furnace (the time from passing through the inlet to passing through the outlet) can be adjusted by adjusting the moving speed of the mixture. The residence time of the mixture in the continuous furnace may be determined according to the temperature in the continuous furnace, the amount of the mixture before heating, etc. The residence time of the mixture in the continuous furnace may be, for example, 10 minutes to 24 hours.

[0103] In the continuous furnace, the temperature may change along the direction of movement of the mixture. For example, the continuous furnace may have a region in which the temperature gradually increases along the direction of movement of the mixture. When the continuous furnace has a region in which the temperature gradually increases, the air may be sent from the higher temperature region to the lower temperature region. The temperature in the continuous furnace (the temperature at any position in the continuous furnace) may be, for example, within a range of room temperature to 2000°C.

[0104] The continuous furnace may have, for example, a low-temperature region that is relatively low temperature in the continuous furnace and is present near the inlet, a temperature-raising region in which the temperature gradually increases from the low-temperature region toward the outlet, a constant temperature region in which the temperature is approximately constant, and a temperature-reducing region in which the temperature gradually decreases from the constant temperature region toward the outlet. The temperature of each region and the volume of the space occupied by each region in the continuous furnace can be appropriately determined depending on the structure of the continuous furnace, the amount of the mixture before heating, the components contained in the gas to be fed, the amount of carbon dioxide generated in the continuous furnace, and the like. The gas feeding in the continuous furnace may be performed in at least one region selected from the group consisting of the low-temperature region, the temperature-raising region, the constant temperature region, and the temperature-reducing region.

[0105] The maximum temperature in the continuous furnace (the maximum temperature among the temperatures at any position in the continuous furnace) may be, for example, equal to or higher than the melting temperature of the activation treatment agent. The maximum temperature in the continuous furnace (the maximum temperature at any position in the continuous furnace) may be, for example, 300 to 900°C, 300 to 700°C, or 300 to 600°C.

[0106] In step (2), the mixture before heating is heated to a temperature equal to or higher than the melting temperature of the activation treatment agent, which produces the following effects. That is, the activation treatment agent in a molten state comes into contact with the positive electrode active material, thereby suppressing deterioration of the crystal structure of the positive electrode active material. In addition, the activation treatment agent can also restore the crystal structure.

[0107] When the molten activation treatment agent comes into contact with a carbon-containing material (such as a carbon-based conductive material or binder), the rate of oxidative decomposition of the conductive material and the binder is increased. Furthermore, when the molten activation treatment agent comes into contact with a fluorine compound derived from the binder and the electrolyte, the fluorine component is stabilized as an alkali metal fluoride, preventing the generation of hydrogen fluoride, which is a corrosive gas, and suppressing deterioration of the crystal structure of the positive electrode active material.

[0108] Furthermore, when the activation treatment agent contains the same alkali metal as the positive electrode active material, it is also possible to supply the alkali metal that is insufficient for the positive electrode active material.

[0109] The maximum temperature in the continuous furnace (the maximum temperature at any position in the continuous furnace) is preferably higher than the melting point of the alkali metal compound contained in the activation treatment agent. The melting point of the alkali metal compound may be lower than the melting point of each alkali metal compound alone by mixing two or more types of alkali metal compounds, and when the activation treatment agent contains two or more types of alkali metal compounds, the eutectic point is taken as the melting point of the alkali metal compound.

[0110] The time for which the mixture is heated to the melting initiation temperature of the activation treatment agent or higher may be determined depending on the amount of the mixture before heating, etc. The time for which the mixture is heated to the melting initiation temperature of the activation treatment agent or higher may be, for example, 1 minute to 24 hours.

[0111] The maximum temperature in the continuous furnace (the maximum temperature among the temperatures at any position in the continuous furnace) may be, for example, not higher than the melting temperature of the activation treatment agent. The maximum temperature in the continuous furnace (the maximum temperature at any position in the continuous furnace) may be, for example, 300 to 600°C, 350 to 575°C, or 400 to 550°C.

[0112] In step (2), the mixture before heating is heated to a temperature below the melting start temperature of the activation treatment agent, thereby suppressing deterioration of the crystal structure of the positive electrode active material due to heating at high temperatures, and making it easier to achieve charge / discharge characteristics equivalent to those of a battery manufactured using an unused positive electrode active material. In addition, the crystal structure can be restored by heating the mixture before heating together with the activation treatment agent. In this specification, "heating to a temperature below the melting start temperature of the activation treatment agent" means heating while maintaining a temperature below the melting start temperature of the activation treatment agent (heating at a holding temperature below the melting start temperature of the activation treatment agent). In addition, "heating to a temperature below the melting start temperature of the activation treatment agent" means not heating at a temperature equal to or higher than the melting start temperature of the activation treatment agent.

[0113] When the heated activation treatment agent comes into contact with a carbon-containing material (such as a carbon-based conductive material or binder), the rate of oxidative decomposition of the conductive material and the binder is increased. Furthermore, when the heated activation treatment agent comes into contact with a fluorine compound derived from the binder and the electrolyte, the fluorine component is stabilized as an alkali metal fluoride, preventing the generation of hydrogen fluoride, which is a corrosive gas, and suppressing deterioration of the crystal structure of the positive electrode active material.

[0114] The time for which the mixture is heated at a temperature lower than the melting initiation temperature of the activation treatment agent may be determined depending on the amount of the mixture before heating, etc. The time for which the mixture is heated at a temperature lower than the melting initiation temperature of the activation treatment agent may be, for example, 1 minute to 24 hours.

[0115] After the heating step, the mixture can be cooled to any temperature, such as about room temperature, as necessary. In this manner, a heated mixture containing a heated positive electrode active material is obtained.

[0116] Step (3): Positive electrode active material recovery step The positive electrode active material recovery step is a step of recovering the heated positive electrode active material from the heated mixture after the heating step (2).

[0117] The mixture after heating contains, in addition to the heated positive electrode active material, components derived from the activation treatment agent (alkali metal compounds, etc.), undecomposed carbon-containing materials (carbon-based conductive materials, binders, etc.), and other undecomposed substances of the positive electrode mixture. In addition, when the positive electrode mixture contains an electrolyte solution containing a fluorine component, the mixture may contain a fluorine component derived from the electrolyte.

[0118] Examples of methods for separating and recovering the heated positive electrode active material from the heated mixture include a solid-liquid separation method in which a solvent such as water is added to the mixture to form a slurry, followed by solid-liquid separation, and a vaporization separation method in which the mixture is heated to vaporize and separate components other than the heated positive electrode active material. The solid-liquid separation method will be described below.

[0119] Step (3a): Solid-liquid separation step Step (3a) is a step of contacting the heated mixture with a liquid containing water to obtain a slurry containing a solid component and a liquid component, and then separating the slurry into the solid component and the liquid component.

[0120] The mixture after heating contains, in addition to the heated positive electrode active material, components derived from the activation treatment agent (alkali metal compounds, etc.), undecomposed carbon-containing materials (carbon-based conductive materials, binders, etc.), and other undecomposed substances of the positive electrode composite. In addition, when the positive electrode composite contains an electrolyte solution containing a fluorine component, the mixture may contain a fluorine component derived from the electrolyte.

[0121] In order to separate and recover the heated positive electrode active material from the heated mixture, a liquid containing water (liquid) is added to the mixture to form a slurry, which is then subjected to solid-liquid separation to separate the solid component and the liquid component.

[0122] The liquid used in the slurrying step is not particularly limited as long as it contains water. The amount of water in the liquid may be 50% by mass or more. In order to increase the solubility of water-soluble components or to increase the processing speed, components other than water may be added to the liquid to adjust the pH. Suitable examples of the liquid containing water include pure water and alkaline cleaning liquid. Examples of the alkaline cleaning liquid include an aqueous solution of at least one anhydride selected from the group consisting of lithium hydroxide, sodium hydroxide, potassium hydroxide, lithium carbonate, sodium carbonate, potassium carbonate, and ammonium carbonate, and a hydrate thereof. Ammonia can also be used as the alkali.

[0123] The resulting slurry contains a solid component mainly containing the positive electrode active material after heating and a liquid component containing water-soluble components other than the positive electrode active material. The liquid component contains an alkali metal component derived from the activation treatment agent and / or a fluorine component derived from the binder and the electrolyte.

[0124] The amount of liquid to be added to the mixture is appropriately determined taking into consideration the amounts of the post-heating positive electrode active material and water-soluble components other than the positive electrode active material contained in the mixture.

[0125] In step (3a), it is preferable to obtain a slurry by stirring the mixture after heating with a liquid containing water. This promotes dissolution of the water-soluble components. The peripheral speed of the tip of the stirring blade is preferably 0.1 to 0.9 m / s.

[0126] The slurry formed in the slurrying step is then subjected to solid-liquid separation. Solid-liquid separation is a step of separating the slurry into a liquid component and a solid component. The method of solid-liquid separation may be a conventional method, such as filtration or centrifugation.

[0127] In step (3a), after the solid-liquid separation, the obtained solid component may be rinsed. Rinsing is an operation in which the obtained solid component is contacted again with a liquid containing water to obtain a slurry, and then the slurry is separated again into a solid component and a liquid component. In step (3a), rinsing may be performed multiple times. The slurry concentration in the rinse may be the same as above.

[0128] In this specification, the positive electrode active material that has undergone steps (1) to (3) is called a recycled positive electrode active material. The recycled positive electrode active material that has undergone steps (1) to (3) can be suitably used for manufacturing a positive electrode or the like. The manufacturing method of the recycled positive electrode active material may include additional steps before and after steps (1) to (3). In this specification, the positive electrode active material that has undergone additional steps other than steps (1) to (3) is also called a recycled positive electrode active material. Examples of the additional steps other than steps (1) to (3) are pre-step (A) and pre-step (B) that are performed before step (1), and the following steps (4) and (5) that are performed after step (3), for example, after step (3a).

[0129] Process (4): Drying process Step (4) is, for example, a step of exposing the solid component obtained in step (3a) to a heating and / or reduced pressure environment to remove water from the solid component.

[0130] The heating temperature is preferably 100°C or higher to remove water. It is more preferably 150°C or higher to remove water sufficiently. In particular, a temperature of 250°C or higher is preferable because the discharge capacity of a battery manufactured using the obtained positive electrode active material is further increased. The temperature in the drying step may be constant, or may be changed stepwise or continuously. The heating temperature range may be, for example, 10°C or higher and less than 900°C.

[0131] The ultimate pressure range of the reduced pressure is, for example, 1.0×10 -10 ~1.0×10 3 It can be Pa.

[0132] Step (5): Annealing (re-firing) step Step (5) may be a step of heat treating the solid component obtained after step (4) at less than 900° C. when the activation treatment agent is heated to a temperature equal to or higher than the melting initiation temperature.

[0133] Step (5) may be a step of heating the solid component after step (4) at a temperature higher than that of step (2) when the activation treatment agent is heated at a temperature lower than the melting initiation temperature. In this case, the temperature at which the mixture after heating is heated may be more than 700° C., 750° C. or higher, 800° C. or higher, 850° C. or higher, or 900° C. or higher, from the viewpoint of vaporizing components other than the positive electrode active material and removing impurities, and from the viewpoint of making it easier to achieve charge / discharge characteristics equivalent to those of a battery manufactured using an unused positive electrode active material by sufficiently increasing the crystallite size of the positive electrode active material.

[0134] The atmosphere for the heat treatment is not limited, but an oxygen-containing atmosphere such as air is preferable. The heat treatment temperature can be 100°C or higher. The heat treatment holding time can be 1 minute to 24 hours. It is particularly preferable to heat at a holding temperature of 350°C or higher for 0.1 to 5 hours.

[0135] The recycled positive electrode active material obtained from the battery mixture by using the method for producing the recycled positive electrode active material of the present invention can be reused in the same way as unused active material. Methods for producing positive electrodes and batteries using recycled positive electrode active materials are well known.

[0136] The final discharge capacity of the recycled positive electrode active material according to the embodiment of the present invention can be 150 mAh / g or more. EXAMPLES

[0137] The present invention will be described in more detail below with reference to examples. However, the present invention is not limited to the following examples unless the gist of the present invention is changed.

[0138] Measurement of the physical properties of the positive electrode active material and the recycled positive electrode active material, and a charge / discharge test using a battery using the positive electrode active material were carried out as follows.

[0139] [Element content] The content of alkali metal elements in the solution and the acid solution in which the powder was dissolved was analyzed using an ICP emission spectrometer (e.g., SPS3000 manufactured by SII NanoTechnology Inc.).

[0140] (Reference example 1) <Production of positive electrodes> The positive electrode described below was prepared by the following procedure. A mixture was obtained by mixing 92 parts by mass of a positive electrode active material (unused positive electrode active material or recycled positive electrode active material), 3 parts by mass of PVdF (binder, manufactured by Kureha Corporation, product number: #1100), and 5 parts by mass of acetylene black (conductive material, manufactured by Denka Co., Ltd., product number: HS100). As the binder PVdF, a binder solution in which PVdF was dissolved in NMP in advance was used. The mixture was kneaded with a rotation-revolution type mixer (ARE-310 manufactured by Thinky Corporation) to prepare a positive electrode mixture paste. NMP was added to adjust the total mass of the positive electrode active material, binder, and conductive material in the positive electrode mixture paste to 50% by mass.

[0141] A 20-μm-thick aluminum foil 1085 (manufactured by Nippon Foil Co., Ltd.) for use as a positive electrode current collector for lithium-ion secondary batteries was attached to one side of the foil in an amount of 3.0 ± 0.1 mg / cm2. 2 The positive electrode composite paste was applied so that the positive electrode was formed as follows: After that, it was vacuum dried at 150°C for 8 hours to obtain a positive electrode. The electrode area of ​​this positive electrode was 1.65 cm 2 It was decided.

[0142] <Battery manufacturing> The coin-type battery described below was fabricated by the following procedure. The above-mentioned positive electrode, electrolyte, separator, and negative electrode were combined to manufacture a non-aqueous electrolyte secondary battery (coin-type battery). The battery was assembled in a glove box with an argon atmosphere. The electrolyte was a mixture of ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate in a volume ratio of 30:35:35, and LiPF 6A solution was used in which the above was dissolved at a ratio of 1.0 mol / L. A laminated film separator in which a heat-resistant porous layer was laminated on a porous film (made of polyethylene) was used as the separator, and metallic lithium was used as the negative electrode.

[0143] <Production of positive electrodes before recycling> The positive electrode active material is Li 1.07 Ni 0.47 Mn 0.48 Fe 0.05 O 2 A positive electrode active material having a crystal structure of R-3m was prepared. The above coin-type battery was produced using this positive electrode active material (unused positive electrode active material), and the following charge / discharge test (rate test) was carried out while maintaining the temperature at 25°C. The 0.2C discharge capacity was 138mAh / g, and the 5C discharge capacity was 106mAh / g. The larger the 0.2C discharge capacity, the higher the rated capacity that can be obtained, and the larger the 5C discharge capacity, the higher the output characteristics that can be obtained. (conditions) Maximum charging voltage: 4.3V Charging current: 0.2mA / cm 2 Charging time: 8 hours Minimum discharge voltage: 2.5V 0.2C discharge current: 0.2mA / cm 2 5C discharge current: 5.0mA / cm 2

[0144] The electrode mixture was mechanically scraped off from the positive electrode used in the above battery, and the electrode mixture was peeled off from the current collector. 5 g of the electrode mixture removed from the positive electrode was treated with 0.1 mol of K per 1 mol of the positive electrode active material as an activation treatment agent. 2 CO 3 and 0.1 mol of Na per 1 mol of positive electrode active material. 2 CO 3 The activation treatment agent had a melting point of 700°C.

[0145] The mixture before heating was placed in an electric furnace and heated in an air atmosphere under conditions of a heating temperature of 700° C. (above the melting start temperature of the activation treatment agent) and a heating time of 240 minutes.

[0146] The mixture after heating was pulverized, and distilled water was added and stirred to obtain a slurry. The obtained slurry was filtered to separate a solid component and a liquid component. The solid component was then collected and dried to obtain a recycled positive electrode active material. The composition, crystal structure, average particle size, and specific surface area of ​​the obtained recycled positive electrode active material were comparable to those of an unused positive electrode active material. The above coin-type battery was produced using the recycled positive electrode active material, and a charge / discharge test was performed under the above conditions while maintaining the temperature at 25°C. The 0.2C discharge capacity was 135mAh / g, and the 5C discharge capacity was 94mAh / g, which was comparable to the discharge capacity of a coin-type battery produced using an unused positive electrode active material.

[0147] (Reference example 2) <Production of positive electrodes before recycling> The positive electrode active material is LiNi 0.33 Co 0.33 Mn 0.33 O 2 A positive electrode active material NCM111 having a crystal structure of R-3m was prepared. When the above coin-type battery was produced using this positive electrode active material (unused positive electrode active material), the initial charge capacity was 178.3mAh / g and the initial discharge capacity (0.2C) was 163.4mAh / g. In addition, when the following charge / discharge test (rate test) was performed while maintaining the temperature at 25°C, the 0.2C discharge capacity was 163.1mAh / g and the 5C discharge capacity was 141.3mAh / g.

[0148] The electrode mixture was mechanically scraped off from the positive electrode of the process waste material generated during the preparation of the above positive electrode, and the electrode mixture was peeled off from the current collector. 5 g of the electrode mixture removed from the positive electrode was treated with 0.1 mol of Li per 1 mol of the positive electrode active material as an activation treatment agent. 2 CO 3 and 0.1 mol of Na per 1 mol of positive electrode active material. 2 SO 4The activation treatment agent had a melting start temperature of 510°C.

[0149] 30 g of the mixture before heating was placed in an electric furnace and heated in an air atmosphere at a heating rate of 300° C. / h, a heating temperature of 450° C. (lower than the melting start temperature of the activation treatment agent), and a heating time of 360 minutes.

[0150] The mixture after heating was pulverized, and distilled water was added and stirred to obtain a slurry. The obtained slurry was filtered to separate a solid component and a liquid component. The solid component was then collected and dried by suction at 100°C for 1 hour.

[0151] The solid component after drying was placed in an electric furnace, and heated in an air atmosphere at a heating temperature of 900°C for 60 minutes to obtain a recycled positive electrode active material after heating. Next, the recycled positive electrode active material after heating was naturally cooled to room temperature, and it was confirmed that the composition, crystal structure, average particle size, and specific surface area of ​​the obtained recycled positive electrode active material were comparable to those of an unused positive electrode active material. When the above coin-type battery was produced using the recycled positive electrode active material, the initial charge capacity was 180.5mAh / g and the initial discharge capacity was 161.1mAh / g. In addition, when the initial charge / discharge (rate test) was performed under the above conditions while maintaining at 25°C, the 0.2C discharge capacity was 160.2mAh / g and the 5C discharge capacity was 133.9mAh / g.

[0152] Example 1 The electrode mixture is mechanically scraped off from the positive electrode prepared above, and the electrode mixture is peeled off from the current collector. K is added as an activation treatment agent to 5 g of the electrode mixture removed from the positive electrode. 2 CO 3 and Li 2 CO 3 The above is mixed in an amount of 0.1 mol and 0.1 mol per mol of the positive electrode active material in the electrode mixture to obtain a mixture (mixture before heating).

[0153] The mixture before heating is carried into a continuous furnace. The continuous furnace is provided with an air inlet on the discharge side of the mixture, and an exhaust port on the inlet side of the mixture. The mixture is heated to a temperature above the melting start temperature (700°C) of the activation treatment agent while air is fed from the air inlet to the exhaust port in the opposite direction to the direction of movement of the mixture in the continuous furnace. The heating in the series of continuous furnaces is controlled so that the temperature gradually increases from the inlet to the discharge port, and the maximum temperature of the continuous furnace is 750°C, the residence time is 24 hours, and the time for heating at a temperature above the melting start temperature (700°C) of the activation treatment agent is 5 hours. At this time, when the carbon dioxide concentration in the gas fed to the continuous furnace is compared with the carbon dioxide concentration in the gas exhausted from the continuous furnace, the carbon dioxide concentration in the gas exhausted from the continuous furnace is higher than the carbon dioxide concentration in the gas fed to the continuous furnace. Next, the mixture discharged from the continuous furnace is naturally cooled to room temperature, and the heated mixture is recovered.

[0154] The mixture after heating is pulverized, distilled water is added and stirred to obtain a slurry. The obtained slurry is filtered to separate it into a solid component and a liquid component. The solid component is then collected and dried at 300°C for 6 hours, the dried solid component is placed in an alumina container, and the container is placed in an electric furnace. Under atmospheric pressure, the temperature is raised from room temperature to 700°C at a heating rate of 300°C / hour while exhausting the atmospheric gas and supplying air, and the solid component is heat-treated at a holding temperature of 700°C for 1 hour (excluding the heating time). After natural cooling to room temperature, a recycled positive electrode active material is obtained. The composition, crystal structure, average particle size, and specific surface area of ​​the obtained recycled positive electrode active material are comparable to those of the positive electrode active material before recycling (unused active material), and the discharge capacity measured in a charge-discharge test using a coin-type battery made using the recycled positive electrode active material is comparable to that of the positive electrode active material before recycling (unused active material).

[0155] In Example 1, contact between high-temperature carbon dioxide and the positive electrode active material can be suppressed by feeding air in the continuous furnace in the opposite direction to the direction of movement of the mixture. Furthermore, by feeding air in the continuous furnace, a part of the carbon dioxide generated by heating in the continuous furnace can be exhausted, and carbon dioxide can be prevented from accumulating in the continuous furnace. As a result, it is possible to produce a recycled positive electrode active material while suppressing deterioration of the positive electrode active material due to high-temperature carbon dioxide.

Claims

1. A method for producing a recycled positive electrode active material, comprising the steps of: (1) A step of mixing a positive electrode mixture containing a positive electrode active material and a carbon-containing material with an activation treatment agent containing one or more alkali metal compounds to obtain a mixture. (2) A step of carrying the mixture into a continuous furnace and heating the mixture while blowing air in a direction opposite to the direction of travel of the mixture to obtain a heated mixture. (3) A step of recovering the heated positive electrode active material from the heated mixture.

2. 2. The manufacturing method according to claim 1, wherein in step (2), when the carbon dioxide concentration in the gas fed into the continuous furnace is compared with the carbon dioxide concentration in the gas exhausted from the continuous furnace, the gas exhausted from the continuous furnace has a higher carbon dioxide concentration.

3. The method according to claim 1 or 2, wherein in the step (2), the mixture is heated to a temperature equal to or higher than a melting point of the activation treatment agent.

4. The method according to claim 1 or 2, wherein in the step (2), the mixture is heated to a temperature below a melting point of the activation treatment agent.

5. The method according to claim 1 or 2, wherein in the step (2), the continuous furnace has a region in which the temperature gradually increases along the traveling direction of the mixture.

6. The method according to claim 1 or 2, wherein the positive electrode active material comprises a lithium compound.

7. The manufacturing method according to claim 1 or 2, wherein the positive electrode active material comprises a composite oxide containing at least one element selected from the following element group 1 and at least one element selected from the following element group 2: Element group 1: Ni, Co, Mn, Fe, Al, and P Element group 2: Li, Na, K, Ca, Sr, Ba, and Mg

8. The method according to claim 1 or 2, wherein the activation treatment agent contains at least one compound selected from the group consisting of potassium compounds and sodium compounds.

Citation Information

Patent Citations

  • Method for recovering active material from discarded battery material

    JP2012186150A

  • Device and method for treating waste lithium-ion battery

    JP2021142475A

  • Apparatus for recovering active material and method for reusing active material by using same

    WO2022045559A1

  • Valuable matter recovery method

    WO2022054723A1